Pengolahan Sampah Organik dengan Teknologi Pengomposan di Kelompok Tani Barokah I Desa Jambangan - Yekti Sri Rahayu; Nurul Muddarisna; Sunyoto; Ani Nurin Ni'mah (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2025)
The processing of organic waste in Jambangan village was burned and transported to another location. Relocation of waste to other sites required high costs, and burning waste gave a risk on respiratory problems and fires in the environment. The Partner Village Development Program aims to provide training in processing organic waste into organic fertilizer for the Barokah I Farmers Group. The method used was training in composting technology for organic waste to produce organic fertilizer. The result showed that organic waste processing in Jambangan village can be carried out by supporting of the farmer groups, village officials and extension workers from the Malang Regency Ministry of Religion Office. Organic waste was obtained from sorting households waste before being used as organic fertilizer. Organic waste of plant stover needs to be chopped into smaller sizes to facilitate the fermentation process. Aerobic composting technology based on chopped plant stover is applied using the stack method and requires a fermentation time of 4 weeks. The fermented compost needs to be sifted to obtain a fine size before being used or packaged. The next program requires assistance in compost production as a fertilizer for agricultural soil in Jambangan village.